1999
DOI: 10.1203/00006450-199907000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Maternal-Fetal Leucine Enrichments in Normal and Intrauterine Growth-Restricted Pregnancies

Abstract: The aim of this study was to compare the fetal/maternal (F/M) leucine-enrichment ratio in normal (AGA) and intrauterine growth-restricted (IUGR) pregnancies at the time of fetal blood sampling (FBS). A maternal primed-constant infusion of L-[1-13C]-leucine was given in six AGA and 14 IUGR pregnancies, divided into three groups according to the pulsatility index (PI) of the umbilical artery and to fetal heart rate (FHR): group 1 (normal FHR and PI, four cases); group 2 (normal FHR and abnormal PI, five cases); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 20 publications
9
62
0
1
Order By: Relevance
“…Previous in vivo studies measured by stable isotope tracers found decreased essential amino acid placental transport rates (5,6), and in vitro experiments confirmed reduced activity of placental amino acid transport systems (10,11) in IUGR and small-for-gestational-age pregnancies as compared with normal pregnancies.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Previous in vivo studies measured by stable isotope tracers found decreased essential amino acid placental transport rates (5,6), and in vitro experiments confirmed reduced activity of placental amino acid transport systems (10,11) in IUGR and small-for-gestational-age pregnancies as compared with normal pregnancies.…”
mentioning
confidence: 77%
“…r educed oxygen and nutrient placental delivery has been clearly demonstrated in intrauterine growth-restricted (IUGR) pregnancies (1)(2)(3)(4)(5)(6)(7). Amino acids are needed during fetal growth for protein synthesis and also for energy production, supplying 20-40% of the fetal-placental unit energy requirements (8).…”
mentioning
confidence: 99%
“…In the industrialized world, alterations in placental blood flow and preeclampsia are leading causes of IUGR so that IUGR due to maternal protein diet restriction may not be relevant. Recent studies, however, suggest that (i) both settings share some striking similarities, since impaired maternal-fetal amino-acid transfer has been observed in human IUGR of vascular origin and (ii) impairment in the placental transport of amino acids has been found precede growth alterations in a rat model of IUGR induced by protein diet restriction (36)(37)(38), implying decreased amino acid transport may be a cause, rather than a consequence, of IUGR in that model. Such evidence therefore argues for the potential relevance of the experimental model used in this study for human IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…30 IUGR is a heterogeneous condition, associated with a specific placental phenotype and with different levels of severity. 31 We have previously shown that a definition of IUGR based on a reduction of growth rate of the abdominal circumference is able to identify fetuses that experience a significant reduction in nutrients delivery and utilization, 32,33 although not invariably hypoxemic and lactacidemic. 10 Moreover, whereas redistribution of blood flows with brain sparing occurs, preliminary data now suggest that the fetus adapts to an inadequate environment also with hypometabolism, reducing oxygen consumption on a per-kilogram basis.…”
Section: Fetal Brain Lactate Detectionmentioning
confidence: 99%